Irish Theatre in Transition From the Late Nineteenth to the Early Twenty-First Century - Morse, D.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
The Irish Theatre in Transition explores the ever-changing Irish Theatre from its inception to its vibrant modern-day reality. This book shows some of the myriad forms of transition and how Irish theatre reflects the changing conditions of a changing society and nation.
Keywords: Theater—History.; Performing arts; Theater; Arts; Theatre History; Performing Arts; Theatre and Performance Studies; Arts